Clinical significance of glutamate metabotropic receptors in renal cell carcinoma risk and survival. (28th November 2018) - Huang, Chao‐Yuan; Hsueh, Yu‐Mei; Chen, Lih‐Chyang; Cheng, Wei‐Chung; Yu, Chia‐Cheng; Chen, Wei‐Jen; Lu, Te‐Ling; Lan, Kuo‐Jin; Lee, Cheng‐Hsueh; Huang, Shu‐Pin; Bao, Bo‐Ying
Abstract: Accumulating evidence suggests the roles of glutamate metabotropic receptors (GRMs) in cancer, in addition to synaptic signalling. The present study assessed the associations of genetic variants in eight GRM genes with regard to risk and overall survival (OS) in 780 renal cell carcinoma (RCC) patients and controls. After adjustment for known risk factors, GRM5 rs7102764 T was associated with an increased risk of RCC ( P = 0.006). Additional analysis has provided evidence that rs7102764 T was correlated with a higher expression of GRM5, which is consistently found to be upregulated in tumours, compared to normal tissues. Furthermore, the GRM3 rs701332 C, GRM4 rs2499707 T, and GRM4 rs4713742 T alleles were significantly associated with a poorer OS ( P ≤ 0.030). The three loci were also observed to have strong cumulative effects on OS. Additional analysis has revealed a significant genotype‐expression correlation of rs2499707 T with increased GRM4 expression, which in turn leads to poorer OS in patients with RCC. GRMs might be involved in RCC development and progression, and genetic variants in GRM s might be promising biomarkers. Abstract : This study assesses the associations of genetic variants in eight glutamate metabotropic receptor (GRM) genes with risk and survival of renal cell carcinoma. It was fond that several variants affect the expression of GRMs, which in turn is correlated with tumour aggressiveness and patient prognosis.